Biologia reprodutiva e genética de astyanax lacrustris: avaliação da razão sexual em cultivo - Garcia, Yasmin [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
In 2018, Brazil produced about 722,560 tons of fish, 74 tons corresponding to the genus Astyanax, which is of great importance due to its properties as a bioindicator of environmental quality and its applicability in population studies. Among it’s species, Astyanax lacustris, popularly known as yellow-tailed lambari, stands out fot its ease of captive management and rapid reproduction. For genetic studies in fish species, microsatellites are highly applied molecular markers due to their codominance and high degree of polymorphism, resulting in eficiente research such as paternity and kinship. The aim of this study was to understand the reproductive biology of the species, testing crossing in different sexual proportions and to analyze how many males and how many females contribute to reproduction, as well as the conditions that influence males, thus enabling and optimizing A. lacustris production in the species pisciculture. The selected proportions were 5:1, 4:2 and 3:3 males: females, respectively, using the seminatural reproduction method. It was concluded that the number of males participating in breeding offspring is variable, as sperm conditions such as motility and concentration significantly influence reproductive capacity, while the female pattern is only one reproducing, regardless of how many are used. Thus, a larger number of males should be used to increase the chances of reproduction, and only one female, which will be responsible for the generation of all offspring.

Em 2018, o Brasil produziu cerca de 722.560 toneladas de peixes, sendo 74 toneladas correspondentes ao gênero Astyanax, o qual apresenta grande importância, devido às suas propriedades como bioindicador da qualidade do ambiente e a sua aplicabilidade em estudos, como os populacionais. Dentre as espécies, Astyanax lacustris, popularmente conhecida como lambari do rabo amarelo, ganha destaque pela facilidade de manejo em cativeiro e rápida reprodução. Para estudos genéticos em espécies de peixes, os microssatélites são marcadores moleculares altamente aplicados devido a sua codominância e alto grau de polimorfismo, resultando em eficientes pesquisas como a de paternidade e parentesco. O objetivo do estudo foi entender a biologia reprodutiva da espécie, testando cruzamentos em diferentes proporções sexuais e analisar quantos machos e fêmeas contribuem na reprodução, bem como as condições que influenciam os machos, para assim viabilizar e otimizar a produção de A. lacustris na piscicultura. As proporções selecionadas foram de 5:1, 4:2 e 3:3 machos: fêmeas, respectivamente, utilizando o método de reprodução seminatural. Concluiu-se que o número de machos que participam gerando descendentes é variável, pois as condições do espermatozoide como motilidade e concentração influenciam significativamente na capacidade reprodutiva, enquanto o padrão de fêmeas é de apenas uma reproduzindo, independente de quantas são utilizadas. Dessa forma, deve-se utilizar um número maior de machos para aumentar as chances de reprodução, e apenas uma fêmea, que será responsável pela geração de todos os descendentes.
Reproductive biology and genetics of astyanax lacrustris: evaluation of the sex ratio in cultivation
Keywords: Pisciculture; Reproduction; Fish; Piscicultura; Reprodução; Peixes-Reprodução; Lambari (Peixe)